Perceived Problem, Partnership, and Training Effect on Productivity and Export: Evidence from Micro and Small Manufacturing Firms in Indonesia - Afin, Rifai (Economics and Finance in Indonesia, 2024)
The primary objectives of this study are threefold: first, to investigate whether the challenges faced by micro and small industries motivate them to enter into partnerships; second, to assess the impact of partnerships on company productivity; and third, to explore the causal relationship between productivity and exports. We aim to determine whether productivity influences exports and vice versa or if a two-way relationship exists. The data used in this study consists of annual survey data from micro and small manufacturing companies, randomly collected by the Central Statistics Agency (BPS) in 2015, with a total sample of 58,290 observations. The methodologies employed include Propensity Score Matching (PSM) to address endogeneity and selection bias issues when measuring the impact of partnerships on productivity. In addition, the Structural Equation Modeling (SEM) framework involves logit regression estimation to assess whether perceived problems influence decisions regarding partnerships and training. The second stage of our analysis employs Two-Stage Least Squares (2SLS) estimation to investigate the simultaneity of productivity and exports. The results indicate that issues related to capital and raw materials significantly motivate companies to engage in partnerships, both in a general context and specific concerning capital and raw materials. Conversely, marketing issues do not significantly influence on marketing partnerships, although they do play a significant role in fostering general partnerships. Meanwhile, issues related to workforce skills do not appear to impact a company’s decision to engage in partnerships or conduct training programs. In terms of production and export estimation, general and specific partnerships demonstrated significantly higher positive impacts on productivity for companies that engage in these collaborative efforts. The 2SLS estimates support the findings from the PSM analysis, confirming that general and specific partnerships improve productivity. Furthermore, the simultaneous relationship estimation reveals a bidirectional relationship between productivity and exports.